Post-activation performance enhancement of flywheel training on lower limb explosive power performance - Fu, Keqi; Chen, Lingying; Poon, Eric Tsz-Chun; Wang, Rou; Li, Qian; Liu, Haochong; Ho, Indy Man Kit (Frontiers in Physiology, 2023)
The study aimed to investigate the post-activation performance enhancement (PAPE) of flywheel training (FT) on lower limb explosive power performance. Using a randomized crossover design, 20 trained men (age = 21.5±1.4 years; training experience 5.5±1.2 years) completed seven main conditions after three familiarization sessions. The first three conditions tested the PAPE of the FT on the counter movement jump (CMJ) under three different inertial loads (0.041 kg•m 2 as L; 0.057 kg•m 2 as ML ; and 0.122 kg•m 2 as P), whereas the following four conditions tested the PAPE of FT on the 30 m sprint, which consisted of three inertial loads (L, ML, and P) and a control condition.Participants were required to perform the CMJ or 30m sprint at baseline (Tb) and immediately (T0), 4 min (T4), 8 min (T8), 12 min (T12), and 16 min (T16) after exercise, respectively. The results of the CMJ conditions showed that PAPE peaked at T4 (p<0.01) and almost subsided at T12 (p>0.05) in ML and P conditions. Meanwhile, PAPE appeared earlier in the P condition, and the effect was more significant (P:ES=1.09; ML:ES=0.79). 30 m sprint results showed significant improvement only in the ML condition. The PAPE peaked at T4 (p<0.05, ES=-0.47) and almost subsided at T8 (p>0.05).It was mainly due to the significant enhancement of the 10-30 m segmental timing performance at T4 (p<0.05, ES=-0.49). This study indicates that the size of the inertial load could influence the magnitude of the PAPE produced by the explosive force of the lower limb. The PAPE of the vertical explosive force increased with increasing inertial load, but the PAPE of the horizontal explosive force did not appear at the maximum inertial load. The most effective elicitation of the PAPE was at 4-8 min after the FT.